1995
DOI: 10.1139/x95-221
|View full text |Cite
|
Sign up to set email alerts
|

Midwinter dehardening of montane red spruce during a natural thaw

Abstract: We documented 3 to 14°C of dehardening in current-year foliage of 10 mature, montane red spruce (Picea rubens Sarg.) trees during a natural thaw from 12 to 21 January 1995. Mean cold tolerance was about -47°C before the onset of thaw conditions, and individuals ranged from -38 to -52OC. After 3 days of thaw, mean cold tolerance dropped to -39"C, with a range of -32 to -44°C. Trees did not regain prethaw levels of cold tolerance until sometime between 31 January and 9 February, or 10 to 20 days after subfreezin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 13 publications
2
49
0
Order By: Relevance
“…For example, Schaberg et al (1996) noted that frost tolerance of seedlings strongly decreased (-47°C to about -33°C) after four to eight days of simulated winter thawing with temperatures above 0°C. Similar reductions in frost tolerance were observed by Strimbeck et al (1995) in mature trees. This rapid dehardening, unique to red spruce, is less pronounced if the period of thawing is brief (DeHayes et al 1990a, Perkins et al 1993 and if night-time temperature remains below 0°C (Hadley and Amundson 1992, Schaberg et al 1996, Lund andLivingston 1998).…”
Section: Frost Susceptibilitysupporting
confidence: 77%
See 1 more Smart Citation
“…For example, Schaberg et al (1996) noted that frost tolerance of seedlings strongly decreased (-47°C to about -33°C) after four to eight days of simulated winter thawing with temperatures above 0°C. Similar reductions in frost tolerance were observed by Strimbeck et al (1995) in mature trees. This rapid dehardening, unique to red spruce, is less pronounced if the period of thawing is brief (DeHayes et al 1990a, Perkins et al 1993 and if night-time temperature remains below 0°C (Hadley and Amundson 1992, Schaberg et al 1996, Lund andLivingston 1998).…”
Section: Frost Susceptibilitysupporting
confidence: 77%
“…For example, the For personal use only. maximum frost tolerance of the current year's foliage is generally -30°C to -50°C (DeHayes et al 1990b;Perkins et al 1993;Strimbeck et al 1995;Schaberg et al 1996Schaberg et al , 2000b), compared to -50°C to -90°C for balsam fir (DeHayes et al 1990b, Strimbeck et al 1995, and -80°C for black spruce and white spruce (DeHayes 1992). This comparatively low frost tolerance would explain why the natural range of red spruce is generally confined to areas with an absolute minimum temperature above -40°C (Arris and Eagleson 1989).…”
Section: Frost Susceptibilitymentioning
confidence: 99%
“…Some researchers believe that the damage is associated with fluctuations of warm and freezing temperatures in winter months (Henson 1952, Cayford et al 1959, Robin and Susut 1974. In the well-studied syndrome of red spruce winter injury in the northeastern United States, both winter desiccation (Curry and Church 1952, Hadley et al 1991 and dehardening/freezing damage (Peart et al 1991;Perkins and Adams 1995;Strimbeck et al 1995;Lazarus et al 2004Lazarus et al , 2006 have been suggested as causal factors. In this paper we examine the possible causes of widespread conifer damage in northern Ontario and identify next steps to improve our understanding of this recurring phenomenon.…”
Section: Ricardo Velasquezmentioning
confidence: 99%
“…in the northeastern United States, both winter desiccation (Curry and Church 1952, Hadley et al 1991 and dehardening/freezing damage (Peart et al 1991;Perkins and Adams 1995;Strimbeck et al 1995;Lazarus et al 2004Lazarus et al , 2006 have been suggested as causal factors. In this paper we examine the possible causes of widespread conifer damage in northern Ontario and identify next steps to improve our understanding of this recurring phenomenon.…”
Section: Ricardo Velasquezmentioning
confidence: 99%
“…1). Mid winter increases the photosynthetic rates of coniferous species occur when there are warm air temperature events [42,43,48,50].…”
Section: Net Photosynthesismentioning
confidence: 99%